KINERJA APARATUR TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR KELURAHAN WALA KECAMATAN MARITENGNGAE KABUPATEN SIDENRENG RAPPANG - nur syawal ashari; Muhammad Rais Rahmat; Abdul Jabbar (PRAJA: Jurnal Ilmiah Pemerintahan, 2020)
Apparatus on the quality of public services in Wala Village, Kecamatang Maritengngae, Sidenreng Rappang Regency. The population in conducting this study were people with male and female gender, amounting to 3,725 people from two environments, the data collection technique used was the Slovin formula with 92 results, taken based on purposive sampling technique. The type of research used is descriptive quantitative research, data collection techniques used are observation techniques, questionnaires, literature study, and documentation. The data analysis technique is using the validity and reliability tests using the SPSS 21.0 application and a Likert scale. Based on the research that was taken from the results of the questionnaire data, it was obtained that the recapitulation of the Apparatus Performance variable with a percentage of 67.4% was included in the "Good" category while the recapitulation of the Public Service Quality variable with a percentage of 69.6% was included in the "Good" category.